Neurolinguistic programming as an international marketing strategy in the leading brands of the interbrand international index 2014 - Laura Giraldo - Paula Lora - Oscar Mahecha - Paula Ruiz (GEON Journal (Management, Organizations and Business), 2015)
The article covers the importance of implementing strategies of Neuro Linguistic Programming in marketing business processes, from internal company policies, to customer communication and brand positioning. The 10 most important companies in the international index interbranding are analyzed, as a method of qualitative and strategic analysis for the implementation of favorable strategies for local companies with interest of internationalize and achieve a more effective and influential level as a recognized brand.
Keywords: International marketing; Interbrand; NLP